Transcriptome analysis of porcine PBMCs reveals lipopolysaccharide-induced immunomodulatory responses and crosstalk of immune and glucocorticoid receptor signaling. Issue 1 (31st December 2021) - Li, Zhiwei; Trakooljul, Nares; Hadlich, Frieder; Ponsuksili, Siriluck; Wimmers, Klaus; Murani, Eduard
ABSTRACT: The current level of knowledge on transcriptome responses triggered by endotoxins and glucocorticoids in immune cells in pigs is limited. Therefore, in the present study, we treated porcine peripheral blood mononuclear cells (PBMCs) with lipopolysaccharide (LPS) and dexamethasone (DEX) separately or combined for 2 hours. The resultant transcriptional responses were examined by mRNA sequencing. We found that the LPS treatment triggered pronounced inflammatory responses as evidenced by upregulation of pro-inflammatory cytokines, chemokines, and related signaling pathways like NF-κB. Concurrently, a series of downregulated pro-inflammatory and upregulated anti-inflammatory molecules were identified. These are involved in the inhibition of TLR, NF-κB, and MAPK cascades and activation of signaling mediated by Tregs and STAT3, respectively. These findings suggested that LPS initiated also an anti-inflammatory process to prevent an overwhelming inflammatory response. The transcriptome responses further revealed substantial crosstalk of immune responses and glucocorticoid receptor (GR) signaling. This was apparent in four aspects: constitutive inhibition of T cell signaling by DEX through a subset of genes showing no response to LPS; inhibition of LPS-induced inflammatory genes by DEX; attenuation of DEX action by LPS paralleled by the regulation of genes implicated in cytokine and calcium signaling; and DEX-induced changes in genes associated with the activation of pro-inflammatory TLR, NF-κB, iNOS, and IL-1 signaling. Consequently, our study provides novel insights into inflammatory and GR signaling in pigs, as well as an understanding of the application of glucocorticoid drugs for the treatment of inflammatory disorders.